Preventive hearing tests in workers exposed to noise and organic solvents - Mariola Śliwińska-Kowalska (Nofer Institute of Occupational Medicine, 2020)
Robust evidence confirms that occupational exposures to organic solvents are ototoxic and can aggravate the effects of noise on the auditory organ. Accordingly, Directive 2003/10/EC of the European Parliament and of the Council recommends that in assessing the risk of occupational hearing loss, the interaction of noise and organic solvents to hearing should be taken into account. Given that no prophylactic recommendations have been established to date, this study is intended to provide physicians with guidance in conducting audiometric tests in workers exposed to noise and organic solvents. The paper discusses the biological effects of noise and organic solvents on the auditory organ and current possibilities of estimating the risk of hearing loss due to isolated exposures to solvents, as well as combined exposures to these chemicals and noise. The scope of medical examination and the significance of individual hearing tests, such as pure-tone audiometry, impedance audiometry, auditory brainstem responses, speech in quiet and speech in noise audiometry, and dichotic digit test, in the diagnostics of solvent-induced hearing loss are presented. An algorithm for conducting hearing tests in workers exposed to organic solvents, and co-exposed to noise and organic solvents, has been proposed depending on the concentration of solvents and noise level. Shown also is the necessity to perform annual audiometric testing in all workers exposed to organic solvents whose concentration in the air exceeds values safe for hearing. In workers exposed to noise and organic solvents, audiometric examinations should be mandatory in all subjects in whom the level of noise exceeds the lower action level defined by Directive 2003/10/EC, which is L EX,8h = 80 dB. Taking into account the detrimental effects of organic solvents to central auditory pathways, in addition to pure-tone audiometry, speech audiometry (preferentially speech in noise) should be included. The introduction of preventive audiometric tests in workers exposed to organic solvents, along with an extension of indications and the scope of hearing tests in workers co-exposed to noise and solvents, is a prerequisite for effective prevention of occupational hearing loss in these professional groups. Med Pr. 2020;71(4):493-505